The impact of the five-factor model of personality on the performance of basketball players - Abbas, I. M. (Frontiers in Sports and Active Living, 2026)
This research examined how the Five-Factor Model (Openness to Experience, Conscientiousness, Extraversion, Agreeableness, and Neuroticism) acts upon professional basketball players, exploring in addition whether these personality traits differ among playing position or levels of experience. A sample frame of 116 male professional players participating in the FIBA Asia Cup 2025 qualification was utilized. Personality traits were assessed using the 41-item Goldberg inventory, while performance was determined through a customized Player Efficiency index based on multiple linear regression analysis of core game statistics (Points, Rebounds, Assists, and Steals). The results indicated statistically Extraversion (a = 0.05); no significant association was found for Agreeableness and Neuroticism. Even though significant differences were found by playing position for Agreeableness, only guards scored less than forwards and centers. Across levels of experience, there were significant differences for Openness to Experience, Conscientiousness, Extraversion, and Neuroticism. Players with more than ten years of experience had higher Openness and Conscientiousness and were lower on Neuroticism than players with five years of experience or less. Overall, the findings suggest that important personality traits—especially openness, self-discipline, and social engagement—can contribute powerfully to basketball performance. These results demonstrate the potential for integrating personality assessment into talent identification, player development programs, and team-building processes in elite basketball settings.